2011
DOI: 10.1007/s00122-011-1620-x
|View full text |Cite
|
Sign up to set email alerts
|

Candidacy of a chitin-inducible gibberellin-responsive gene for a major locus affecting plant height in rice that is closely linked to Green Revolution gene sd1

Abstract: Appropriate plant height is crucial for lodging resistance to improve the rice crop yield. The application of semi-dwarf 1 led to the green revolution in the 1960s, by predominantly increasing the rice yield. However, the frequent use of single sd1 gene sources may cause genetic vulnerability to pests and diseases. Identifying useful novel semi-dwarf genes is important for the genetic manipulation of plant architecture in practical rice breeding. In this study, introgression lines derived from two parents cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…In the study, we identified and delimited a major QTL for seedling shoot length, qSSL1b within 80.5 kb region on chromosome 1, where 16 genes were annotated (Table 5), including the candidate gene for ph1 , a major locus affecting plant height in rice encoding a chitin-inducible gibberellin-responsive protein (Kovi et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we identified and delimited a major QTL for seedling shoot length, qSSL1b within 80.5 kb region on chromosome 1, where 16 genes were annotated (Table 5), including the candidate gene for ph1 , a major locus affecting plant height in rice encoding a chitin-inducible gibberellin-responsive protein (Kovi et al . 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the qSD1-2 region was reported for the semidwarf1 (sd1) gene, the plant height QTLs CULM LENGTH 1a (qCL1a), qCL1b, ph1, and qPH1, and the QTLs associated with root, seedling, and panicle growth, flowering time, and seed setting (Asano et al, 2011;Kovi et al, 2011;Mispan et al, 2013;Zhang et al, 2013). Thus, the objectives of this research were (1) to isolate the qSD1-2 underlying gene from the multi-QTL region and confirm its functions; (2) to identify the molecular and physiological mechanisms of dormancy development regulated by the cloned and confirmed gene; and (3) to determine the origin, distribution, and functional differentiation of major alleles at the seed dormancy locus.…”
mentioning
confidence: 99%
“…Markers on the partial map of chromosome 1 were aligned against the Nipponbare genome sequence (IRGSP 2005) and used to select recombinants (Rec.1-1 to -3) to dissect the initial introgression segment from SS18-2 (black bar in the top panel) in the EM93-1 background (empty bars). OsVp1 , ortholog of the Maize VIVIPAROUS1 gene; ph1 , plant height QTL proposed to be Os01g65900 (Kovi et al 2011); and sd1 (k), marker targeting the 383-bp functional deletion within the sd1 semidwarf gene (Monna et al 2002); N, the number of plants in a recombinant-derived progeny line; r g and r h , marker-trait correlation coefficients for germination ( r g ) or plant height ( r h ), with a significant value (*** for P < 0.0001 and ns for P = 0.05 or greater) indicating that the SS18-2-derived allele at locus or loci on the marked heterozygous region increased germination or plant height. Vertical lines delimit qSD1-2/qPH1 , based on the progeny testing.…”
Section: Resultsmentioning
confidence: 99%
“…However, differences between the OsGA20ox2 wild-type and mutant genotypes for the GA level in developing and imbibed seeds and for the degree of seed dormancy were not determined, which could have contributed to the uncertainty about the role of GA in regulating germination in rice (Steber 2007). The plant height QTL ph1 was mapped onto the qSD1-2/qPH1 region of <400 kb and proposed to be the locus Os01g65900 encoding a predicted chitin-inducible GA-responsive protein (Kovi et al 2011). Research is being conducted to characterize the regulatory role of OsGA20ox2 in dormancy development and release and to determine if Os01g65900 also contributes an effect to qPH1 ,or qSD1-2 , or both.…”
Section: Discussionmentioning
confidence: 99%